Parvalbumin Interneurons Shape Neuronal Vulnerability in Blunt TBI. (17th May 2018) - Chandrasekar, Akila; Heuvel, Florian olde; Tar, Lilla; Hagenston, Anna M; Palmer, Annette; Linkus, Birgit; Ludolph, Albert C; Huber-Lang, Markus; Boeckers, Tobias; Bading, Hilmar; Roselli, Francesco
Abstract: Excessive excitation has been hypothesized to subsume a significant part of the acute damage occurring after traumatic brain injury (TBI). However, reduced neuronal excitability, loss of neuronal firing, and a disturbed excitation/inhibition balance have been detected. Parvalbumin (PV) interneurons are major regulators of perisomatic inhibition, principal neurons firing, and overall cortical excitability. However, their role in acute TBI pathogenic cascades is unclear. We exploited the chemogenetic Pharmacologically Selective Activation Module and Pharmacologically Selective Effector Module control of PV-Cre + neurons and the Designer Receptors Exclusively Activated by Designer Drug (DREADD) control of principal neurons in a blunt model of TBI to explore the role of inhibition in shaping neuronal vulnerability to TBI. We demonstrated that inactivation of PV interneurons at the instance or soon after trauma enhances survival of principal neurons and reduces gliosis at 7 dpi whereas, activation of PV interneurons decreased neuronal survival. The protective effect of PV inactivation was suppressed by expressing the nuclear calcium buffer PV-nuclear localisation sequence in principal neurons, implying an activity-dependent neuroprotective signal. In fact, protective effects were obtained by increasing the excitability of principal neurons directly using DREADDs. Thus, we show that sustaining neuronal excitation in the early phases of TBI may reduce neuronal vulnerability by increasing activity-dependent survival, while excess activation of perisomatic inhibition is detrimental to neuronal integrity.